The impacts of oil shocks on Malaysia's GDP growth - Yip, Chee Yin; Lim, Hock Eam; Golam Hassan, Asan Ali (School of Mathematical Sciences, Universiti Sains Malaysia, 2009)
This paper suggests that instrumental variable regression is a good alternative to nonlinear specification model when estimating the impacts of oil shocks on GDP growth in Malaysia.